Analisa Faktor Keberhasilan Wirausaha pada UMKM Jaya Boga Donuts - Rengganis, Diaz Ayu (Maliki Interdisciplinary Journal, 2024)
Business ventures have grown rapidly in various fields. The development of this business world has encouraged the birth of micro, small and medium enterprises or MSMEs in the culinary field. The development of MSMEs in the culinary field has also become a new field of work for the community. Many entrepreneurs then began to expand their wings in pioneering culinary businesses starting from main meals, snacks, and desserts. In the business world, of course, there are factors that influence the success of the business. Successful entrepreneurs must go through a long process to achieve success. There are many factors that influence the success of a business, both internal and external factors. This study aims to determine the entrepreneurial success factors that influence the success of UMKM Jaya Boga Donuts. Research using descriptive analysis method with a qualitative approach. This research was conducted at UMKM Jaya Boga Donuts which is located in Ngromo Village, Nawangan District, Pacitan Regency. The data collection technique uses the interview method with informants who are the owners of Jaya Donuts himself. From the data obtained, it can be concluded that the success of UMKM Jaya Boga Donuts, which now has two branches, is more or less influenced by factors of motivation, experience, education, as well as applying the principles of tenacity, perseverance and focus on goals.